Bilateral quadratus lumborum block for management of persistent postoperative paralytic ileus: a case report - Carlos Rodrigues Almeida; Pedro Cunha (Brazilian Journal of Anesthesiology, 2021)
We report the case of a 62-year-old female who suffered from a persistent postoperative paralytic ileus following an urgent open cholecystectomy. On the fifth postoperative day we performed a bilateral Quadratus Lumborum Block (QLB) type 1 which resulted in a progressive resolution of the condition. This case report highlights that QLB is not only limited to somatic pain control, but it can also be used to alleviate visceral pain, namely in the context of paralytic ileus management in the postoperative period.